In silico and in vivo models for Qatari‐specific classical homocystinuria as basis for development of novel therapies. Issue 2 (23rd November 2018) - Ismail, Hesham M.; Krishnamoorthy, Navaneethakrishnan; Al‐Dewik, Nader; Zayed, Hatem; Mohamed, Nura A.; Giacomo, Valeria Di; Gupta, Sapna; Häberle, Johannes; Thöny, Beat; Blom, Henk J.; Kruger, Warren D.; Ben‐Omran, Tawfeg; et al.
Abstract: Homocystinuria is a rare inborn error of methionine metabolism caused by cystathionine β‐synthase (CBS) deficiency. The prevalence of homocystinuria in Qatar is 1:1, 800 births, mainly due to a founder Qatari missense mutation, c.1006C>T; p.R336C (p.Arg336Cys). We characterized the structure–function relationship of the p.R336C‐mutant protein and investigated the effect of different chemical chaperones to restore p.R336C‐CBS activity using three models: in silico, Δ CBS yeast, and CRISPR/Cas9 p.R336C knock‐in HEK293T and HepG2 cell lines. Protein modeling suggested that the p.R336C induces severe conformational and structural changes, perhaps influencing CBS activity. Wild‐type CBS, but not the p.R336C mutant, was able to restore the yeast growth in Δ CBS ‐deficient yeast in a complementation assay. The p.R336C knock‐in HEK293T and HepG2 cells decreased the level of CBS expression and reduced its structural stability; however, treatment of the p.R336C knock‐in HEK293T cells with betaine, a chemical chaperone, restored the stability and tetrameric conformation of CBS, but not its activity. Collectively, these results indicate that the p.R336C mutation has a deleterious effect on CBS structure, stability, and activity, and using the chemical chaperones approach for treatment could be ineffective in restoring p.R336C CBS activity. Abstract : Homocystinuria prevalence is high in Qatar (1:1, 800) due to a founder Qatari missense mutation, c.1006C>T; p.R336C (p.Arg336Cys), in the CBS protein. Protein modeling suggest that p.R336C induces severe conformational changes; a large shift in the secondary structure, increasing the intramolecular H‐bonds, and enlargement in the mutational spot (due to reduction of formed H‐bond around cysteine) that appears like a cavity. Consequently, these changes leads to reduce the CBS stability and activity. Our yeast and cell culture models confirmed these observations.